Crazy Horse : young war chief - Stanley, George Edwardfrey50; Henderson, Meryl (New York : Aladdin Paperbacks, 2005)
Presents a brief biography of Crazy Horse, the Oglala Sioux chief who fought for the rights of Native American people and who led the defeat of General Custer at Little Big Horn in 1876.
Great Sioux nation -- Curly -- Special bow -- Magic deer -- Raid on conquering Ber's camp -- Vision -- We only want peace -- Crazy Horse -- Our sacred land -- Old ways -- Reservations -- Battle of the Little Bighorn -- End of the struggle -- For more information.
Keywords: Crazy Horse, -- approximately 1842-1877; Crazy Horse, -- approximately 1842-1877.; Oglala Indians -- Kings and rulers; Dakota Indians -- Wars, 1876; Little Bighorn, Battle of the, Mont., 1876; Kings, queens, rulers, etc; Oglala Indians; Indians of North America -- Great Plains; Montana; Biography; Juvenile works